2019
DOI: 10.1080/00207179.2019.1569763
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting natural dynamics for gait generation in undulatory locomotion

Abstract: Robotic vehicles inspired by animal locomotion are propelled by interactive forces from the environment resulting from periodic body movements. The pattern of body oscillation (gait) can be mimicked from animals, but understanding the principles underlying the gait generation would allow for flexible and broad applications to match and go beyond the performance of the nature's design. We hypothesize that the traveling-wave oscillations, often observed in undulatory locomotion, can be characterized as a natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Contrarily, in [ 24 ] for dry frictional environment, it is found that at resonance, the speed of undulatory locomotion decreases and the power increases. More recently, in [ 37 ], for viscous friction, the resonance frequency is defined as the frequency at which the speed of a system is maximized with minimum actuation effort for undulatory locomotion. In this section we study the correlation between the input frequency and the resulting speed.…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, in [ 24 ] for dry frictional environment, it is found that at resonance, the speed of undulatory locomotion decreases and the power increases. More recently, in [ 37 ], for viscous friction, the resonance frequency is defined as the frequency at which the speed of a system is maximized with minimum actuation effort for undulatory locomotion. In this section we study the correlation between the input frequency and the resulting speed.…”
Section: Resultsmentioning
confidence: 99%
“…The author emphasizes that the analytical fluid force model ( 4) is greatly simplified and cannot, for example, describe the pressure or shear force variation across the wings or body obeying the Bernoulli's principle as shown in figures 14(a) and (b) in [16] or other hydrodynamic characteristics of the swimming. It is only used in our study as well as other studies [21,23,[32][33][34][35]37] to give an approximation of the fluid force acting on the wing or body in the study of wing-or body-fluid interaction which allows us to study the response of wing kinematics to the tension and fluid force, to investigate the influence of resonance exploitation of wing natural modes on wing oscillation amplitude, the total thrust and the muscle power consumption, and to derive the analytical relationships of swimming kinematics and kinetics (the results in sections 4.1 and 4.2). For example, simulation showed that when the actuation frequency of the wing was 0.5 Hz, off the resonance frequency 0.29 Hz, the peak power of the middle tensegrity fin rays increased by more than 70%, but both the wing peak-to-peak oscillation .…”
Section: Determination Of Added Mass Coefficientmentioning
confidence: 99%
“…By synchronizing body undulation frequency with the flow, fish swim efficiently, harnessing energy from the fluid and converting it into propulsion (Beal et al, 2006; Akanyeti et al, 2016; Liao and Akanyeti, 2017). The oscillation of the caudal fin emerges as one of the most efficient propulsion modes in terms of transport costs (Rayner, 1986; Ludeke and Iwasaki, 2019), and underwater speeds are enhanced significantly (Block et al, 1992), resulting in passive propulsion even in deceased fish specimens (Liao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%